2006
DOI: 10.1097/01.tp.0000208801.51222.bd
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cells Activated by Lipopolysaccharide after Dexamethasone Treatment Induce Donor-Specific Allograft Hyporesponsiveness

Abstract: Alternatively activated DC are more efficacious than the classical imDC in the regulation of the alloimmune response, which may be related to a distinct cytokine profile characterized by an increased IL-10/IL12 ratio.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
58
0
6

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 39 publications
3
58
0
6
Order By: Relevance
“…Priming with Dex-DC leads to a decrease in the number of IFN-g-producing cells, while increasing the number of IL-10 producing cells both in vivo and in vitro, which could point to the induction of Tr1-like Treg [16,19]. In line with this, an up-regulation of FoxP3 expression marking Treg in mice was recently observed in lymph node cells upon in vivo treatment with Dex-DC [18]. However, conclusive data on functional involvement of Treg induced by Dex-DC are lacking.…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…Priming with Dex-DC leads to a decrease in the number of IFN-g-producing cells, while increasing the number of IL-10 producing cells both in vivo and in vitro, which could point to the induction of Tr1-like Treg [16,19]. In line with this, an up-regulation of FoxP3 expression marking Treg in mice was recently observed in lymph node cells upon in vivo treatment with Dex-DC [18]. However, conclusive data on functional involvement of Treg induced by Dex-DC are lacking.…”
Section: Introductionsupporting
confidence: 61%
“…In addition, Dex-DC possess durable immaturity [10] as high IL-10 and little IL-12 production was maintained up to 5 days after removal of Dex. In vivo, application of Dex-DC prior to allograft transplantation significantly prolonged the survival of the grafts in an antigendependent fashion in mice [16,18]. Priming with Dex-DC leads to a decrease in the number of IFN-g-producing cells, while increasing the number of IL-10 producing cells both in vivo and in vitro, which could point to the induction of Tr1-like Treg [16,19].…”
Section: Introductionmentioning
confidence: 99%
“…BALB/c (H-2 d ) and CBA (H-2 k ) mice ages 8-10 weeks were purchased from Charles River (Maastricht, The Netherlands) and maintained under specific pathogen-free conditions and handled according to the guidelines of the local ethics committee of the Radboud University Nijmegen. Bone marrow-derived DCs were obtained by culturing bone marrow from BALB/c mice as previously described (30,31). Briefly, bone marrow was flushed from femur and tibia and cultured for 8 days in 6-well plates (1 ϫ 10 6 cells/well; Corning Costar, Badhoevedorp, The Netherlands) containing RPMI 1640 DM medium (Invitrogen Life Technologies, Breda, The Netherlands) with 10% fetal calf serum (FCS; Greiner Bio One, Alphen aan den Rijn, The Netherlands), 1% pyruvate, 1% Glutamax, 1% penicillin/streptomycin (all from Invitrogen Life Technologies), and 20 ng/ml granulocytemacrophage colony-stimulating factor (Pepro-Tech, London, (32,33) were cultured in complete RPMI 1640 DM medium supplemented with 15% WEHI-3B-conditioned medium as a source of murine IL-3 (DSMZ, Braunschweig, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Addition of 1 g/ml lipopolysaccharide (LPS) (L4391; Sigma-Aldrich) was used as a positive control for maturation of DCs. After 14 hours of incubation, cells were harvested and subjected to direct or indirect fluorescence staining of cell surface markers, essentially as described previously (31). Briefly, cells were stained with anti-CD40 (clone FGK45.5; Miltenyi Biotec, Utrecht, The Netherlands) or isotype-matched control antibodies (R35-95; BD PharMingen), followed by phycoerythrin (PE)-conjugated goat anti-F(abЈ) 2 anti-rat (Beckman Coulter, Bedfordshire, UK) and Alexa 647-conjugated anti-CD11c (N418; Serotec, Oxford, UK), or with PE-conjugated anti-CD86 (PO3.1; eBioscience, Malden, The Netherlands) and Alexa 647-conjugated anti-CD11c.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, it was previously demonstrated that DCs treated with synthetic drugs or pathogen-derived extracts acquire immature phenotype and upon adoptive transfer suppress the severity of collagen-induced arthritis, mouse kidney grafts and experimental autoimmune encephalomyelitis (EAE). [13][14][15][16][17][18][19][20][21][22] The mechanisms of DC-induced suppression are mostly dependent on the generation of Treg cells in vivo. 17 EAE is a T-cell-dependent neuroinflammation that, in many aspects, mimics human multiple sclerosis.…”
Section: Introductionmentioning
confidence: 99%